Evaluasi Implementasi Program Ujian Madrasah Di Kecamatan Cipanas Dengan Menggunakan Discrepancy Evaluation Model - Tuti Haryati; Ella Padilah; Yuyun Elizabeth Patras (JURNAL MANAJEMEN PENDIDIKAN, 2023)
IMPLEMENTATION EVALUATION OF THE MADRASAH EXAM PROGRAM IN CIPANAS DISTRICT USING DISCREPANCY EVALUATION MODELThe research is to evaluate the madrasah final test program for the madrasah ibtidaiyah learner (MI) in the Cipanas sub-district. The government policy by eliminating the national exam (UN) can be replaced by arranging the madrassah/school exams that are returned to each school unit. The research method used is a qualitative descriptive method using discrepancy models. Data collection techniques using interviews, observation, and documentation. Several steps taken in data analysis include data collection, data reduction, display data, and verification. The study is trying to answer how implementation evaluations of madrasah exam programs in the Cipanas sub-district and Cianjur Regency. Researchers found that (1) The program design, composed by MI Assaidiyyah, MI Mifathul Falah, and MI Futuuhiyah, has been effectively prepared for the 2021/2022 madrasah's exam; (2) The complete application of the madrasah's exam program has been by the standard set by the government in SK Dirjen Pendis No. 455 the year 2022; (3) The evaluation process by MI Assaidiyyah, Miftahul Falah and MI Futuuhiyah shows a rather accurate data; (4) The madrasah's exam program performed in 2021/2022 matched and achieved the desired and foreordained goal; (5) Students' general achievement can be achieved which has been appointed.